Efficacy of brief guided self-help cognitive behavioral treatment for perfectionism in reducing perinatal depression and anxiety: a randomized controlled trial - Lowndes, T.; Egan, Sarah; McEvoy, P. (Routledge, 2018)
Perfectionism has been proposed as a transdiagnostic process that maintains depression and anxiety through shared cognitive and behavioral processes. The purpose of this study was to investigate the efficacy of a brief, guided cognitive behavioral treatment (CBT) for perfectionism delivered via a self-help booklet in reducing perfectionism and symptoms of depression and anxiety during the antenatal period. Pregnant women in their third trimester were randomly allocated to self-help (n = 30) or waitlist control (n = 30). There were significant reductions in perfectionism and symptoms for participants who received CBT for perfectionism from pre- to post-treatment, which were maintained at 3-month follow-up, while the waitlist control group demonstrated no significant changes. Path analysis demonstrated a significant indirect effect of treatment condition on post-treatment depression and anxiety scores via perfectionism, controlling for pre-treatment scores, suggesting changes in perfectionism were associated with decreases in symptoms. The findings suggest that it would be useful for future research with larger samples to further investigate the efficacy of CBT for perfectionism for perinatal depression and anxiety.